THE CONCEPT OF MARRIAGE IN THE QUR'AN - Andi Fadhil Andi Aderus; Mardan; Muh Yusuf (PT. Jurnal Center Indonesia Publisher, 2025)
Marriage is a sunnatullah that occurs between living creatures, especially for humans in pairs. The Qur'an explains the concept of marriage quite specifically in the scope of Sakinah, Mawadah, and Rahmah. Deep meaning of these three concepts can be explored with the aim of maximizing the worship of marriage in it. In addition to the fulfillment of rights and obligations, the legal scope of marriage also has its own position as a discussion that is quite interesting to explore.